From the chivalrous language - Roca, Deodoro (Universidad Nacional de Córdoba, 1916)
The article talks about how childhood stories and legends influence the imagination and how reality is transformed into something fantastic. It is a reflection on the importance of imagination and emotion in our lives. The author invites us to reconstruct the past and find beauty in the simplest places.